HUBUNGAN TINGKAT PENGETAHUAN DAN SELF MANAGEMENT DENGAN KUALITAS HIDUP PENDERITA DIABATES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS KELURAHAN PONDOK KELAPA JAKARTA TIMUR - Suci Meliyani (2022)
Diabetes Mellitus is a chronic disease that is a serious problem in the world because every year incidence is increasing. Quality of life people with diabetes is main goal of treatment, because if the quality of life is low and there are problems someone due to lack of knowledge or poor self-management, it can exacerbate metabolic disorders either directly or indirectly through complications. This study aims to determine level of knowledge and self-management with quality of life in patients with type 2 diabetes mellitus. Using the Chi-Square test with a cross sectional approach, with a purposive sampling technique, a sample of 108 respondents. Data were collected using the Diabetes Knowledge Questionnaire (DKQ-24), Diabetes Self Management Questionnaire (DSMQ), and WHOQOL_BREF uality of life. These three questionnaires have been tested for validity and reliability. Chi-Square test results obtained p-value = 0.003 or <0.05 which indicates a relationship between the level of knowledge with quality of life and p-value = 0.018 or <0.05 which indicates a relationship between self-management and quality of life in patients patients with type 2 diabetes mellitus in the working area of the Pondok Kelapa Village Public Health Center